Maintenance Study of Rail Track Structure for Temporary Track at Electrified Double Track Project (EDTP) Gemas-JB - binti Mat Zahari, Nur Intan Amira; Ts. Dr. Joewono Prasetijo (Progress in Engineering Application and Technology, 2022)
Because some sections of the new double track alignment overlap or are extremely close to current operating KTMB track and need infra building to acquire ownership of such sections, required construction operations must be progressed accordingly. Even though these are temporary tracks, the quality must be maintained at the greatest level, as this includes the passengers' safety as well as the running train itself. The track maintenance team is responsible for keeping the track in proper working order for the operating train. And, using the data acquired, the researcher extracts and filters the data so that the track quality value may be provided in the best way possible and the track can be effectively monitored. The results of the track monitoring model were given, and a discussion about track quality was held resulting in using this track monitoring methodology, the maintenance staff will always receive an early warning about the track conditions for each week that the survey data is gathered, which can be addressed quickly and maintain the track in safe condition for the track and the running track. By the completion of this research, all involved will have gained more knowledge and will be able to enhance site implementation for future projects.